Antioxidant properties of the extracts of vine tea (Ampelopsis grossedentata) with the different color characteristics and inhibition of rapeseed and sunflower oil oxidation. (January 2021) - Jia, Caihua; Li, Jinghuan; Zhang, Mingxing; Ma, Weibo; Zhao, Siming; Liu, Ru; Rong, Jianhua; Li, Xiaohua
Abstract: An effective antioxidant is crucial to prevent deterioration of lipid. This study aimed to investigate the antioxidant properties of vine tea extracts and evaluate their inhibition effect on lipid oxidation. In this study, total flavonoids, phenolics, and anthocyanins content of four leaf extracts were determined from leaves of different ages and colors. In addition, the antioxidant ability of these extracts was evaluated by determining the ferric reducing antioxidant power, DPPH· and OH scavenging activity, and lipid peroxidation inhibitory activity. The results revealed that the extracts, especially from young leaf samples, could effectively scavenge radicals and inhibit lipid oxidation, indicating their antioxidant ability. Compared to BHT, vine tea extracts significantly inhibited the increase of POV and TBARS in sunflower and rapeseed oils. This result may be vital for searching natural antioxidants that prolong the shelf life of food products. Highlights: The young leaves of A. grossedentata contained higher flavonoids content. The anti-oxidation of GYL, GOL, RYL & ROL are evaluated in different oils. The level of oxidation products and fatty acids were determined with 1 H-NMR. The leaf extracts showed a better effect on retarding oil oxidation than BHT.